2019
DOI: 10.3390/jcm8030344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Teriflunomide and Dimethyl Fumarate on Cortical Atrophy and Leptomeningeal Inflammation in Multiple Sclerosis: A Retrospective, Observational, Case-Control Pilot Study

Abstract: Background: Pathologic changes in cortical gray matter (GM) and leptomeninges contribute to disability worsening in patients with multiple sclerosis (MS), but there is little evidence whether disease-modifying treatments can slow down cortical pathology in MS. Objectives: To investigate the effect of teriflunomide (TFM) and dimethyl fumarate (DMF) in reducing cortical pathology, as determined by percentage cortical volume change (PCVC) and leptomeningeal contrast enhancement (LMCE) on MRI. Methods: This was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 53 publications
3
24
0
Order By: Relevance
“…Numerical reductions in CGM and WB atrophy with teriflunomide versus placebo were apparent in both subgroups, although many comparisons did not reach statistical significance, potentially due to small numbers of patients in the subgroups and the relative resistance of CGM to pseudoatrophy compared with WB as we have previously shown. 15 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerical reductions in CGM and WB atrophy with teriflunomide versus placebo were apparent in both subgroups, although many comparisons did not reach statistical significance, potentially due to small numbers of patients in the subgroups and the relative resistance of CGM to pseudoatrophy compared with WB as we have previously shown. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these results extend previous findings of a reduction in brain atrophy with teriflunomide in patients with relapsing MS to those patients with CIS, and align with new data suggesting that teriflunomide-treated MS patients had slower rates of whole brain, GM, WM, and thalamic atrophy over 12 months versus age- and sex-matched healthy controls. 14 16 , 21 Moreover, compared with dimethyl fumarate, a recent head-to-head study suggested that teriflunomide had a superior effect on the preservation of CGM and WB volume over 15−24 months. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations